2022
DOI: 10.1186/s13690-022-00997-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of unmet need for contraception among women in low and high-priority segments for family planning demand generation in Nigeria

Abstract: Background Studies have identified various determinants of unmet need for contraception. These determinants cut across individual, household, community, and health facility levels. Despite this evidence, there remains a lack of information regarding differentials in the prevalence and determinants of unmet need for contraception among women in the low-priority segments (such as women of advanced reproductive age and women living with disabilities) and high-priority segments (such as adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 59 publications
2
2
1
Order By: Relevance
“…This study also revealed regional disparities in the unmet need for family planning. This finding is consistent with previous findings [ 4 , 10 , 12 , 20 ]. Although difficult to explain, the disparities in region/geo-political zones might be mainly due to culture, socioeconomic inequalities, religion, lack of access to and attitudinal resistance to certain contraceptive methods in some regions/geo-political zones compared to others.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This study also revealed regional disparities in the unmet need for family planning. This finding is consistent with previous findings [ 4 , 10 , 12 , 20 ]. Although difficult to explain, the disparities in region/geo-political zones might be mainly due to culture, socioeconomic inequalities, religion, lack of access to and attitudinal resistance to certain contraceptive methods in some regions/geo-political zones compared to others.…”
Section: Discussionsupporting
confidence: 94%
“…The study also revealed a negative relationship between women in the richest wealth category and unmet need for family planning. This finding is in line with previous studies [ 4 , 10 ] which report an inverse relationship between unmet need for family planning and high household wealth. Lack of access and cost of procuring contraceptive methods among other constraints, faced by the poor women compared to their richest counterparts might explain this relationship.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations